Evaluation of acid digestion techniques to estimate chromium contents in cattle feces - Rocha, Gabriel Cipriano; Palma, Malber Nathan Nobre; Detmann, Edenio; Valadares Filho, Sebastião de Campos (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the accuracy of digestion techniques using nitric and perchloric acid at the ratios of 2:1, 3:1, and 4:1 v v‑1, in one‑ or two‑step digestion, to estimate chromium contents in cattle feces, using sodium molybdate as a catalyst. Fecal standards containing known chromium contents (0, 2, 4, 6, 8, and 10 g kg‑1) were produced from feces of five animals. The chromium content in cattle feces is accurately estimated using digestion techniques based on nitric and perchloric acids, at a 3:1 v v‑1 ratio, in one‑step digestion, with sodium molybdate as a catalyst.